2012
DOI: 10.1590/s1516-635x2012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary arginine supplementation on broiler breeder egg production and hatchability

Abstract: This study investigated the effects of arginine (Arg) supplementation on broiler breeder egg production and egg quality. Male (30) and female (360) Ross ® breeders, totaling 390 birds, were studied. A completely randomized design with five Arg levels (0.943%, 1.093%, 1.243%, 1.393%, 1.543% digestible Arg) and six replicates of 12 females and one male per experimental unit was applied. The following performance and egg quality were evaluated: lay percentage, albumen and yolk contents, average egg weight, egg sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
4
27
1
1
Order By: Relevance
“…Dietary L-Arg (g/kg of the diet) SEM 0.000 0 These results are in accordance with the findings of Silva et al [12] who reported that L-Arginine supplementation had a positive effect on egg production and hatchability in breeders. In this regard, it is well documented that dietary L-Arg might be potentially used to improve the fertility of broiler breeder hens due to the sperm penetration in the perevitelline membrane [13].…”
Section: Traitssupporting
confidence: 90%
“…Dietary L-Arg (g/kg of the diet) SEM 0.000 0 These results are in accordance with the findings of Silva et al [12] who reported that L-Arginine supplementation had a positive effect on egg production and hatchability in breeders. In this regard, it is well documented that dietary L-Arg might be potentially used to improve the fertility of broiler breeder hens due to the sperm penetration in the perevitelline membrane [13].…”
Section: Traitssupporting
confidence: 90%
“…In addition to improving production performance, adequate essential amino acid supplementation promotes better internal and external egg quality (Novak et al, 2004;Silva et al, 2012). This effect was observed in the present study, in which egg mass increased with arginine supplementation and presented a quadratic behavior up to 1048 mg of digestible arginine addition per kg of feed.…”
Section: Discussionsupporting
confidence: 77%
“…Considering sparing effect of arginine by GAA, Basiouni et al [30] showed that dietary inclusion of 1.5% digestible arginine to laying hen diet KHAKRAN, CHAMANI, FOROUDI SADEGHI, AFSHAR increased production from 52% to 67.86%. Silva et al [31] reported that dietary inclusion of arginine increased EP in broiler breeders. Sparing effect of arginine by GAA may be reason for improving performance in birds which it was found in studies on broiler chicks [29] .…”
Section: Discussionmentioning
confidence: 99%